Building the Spirit of Nationalism through Culture-Based Learning in Elementary Schools: A Comparative Study of Indonesia and Türkiye - Mustoip, Sofyan; Fadhlullah, Muhammad Ziyad Fakhri (LJPI UI Bunga Bangsa Cirebon, 2025)
This study explores the role of culture-based learning in fostering nationalism among elementary school students in Indonesia and Türkiye. Objective: This study aims to analyze and compare the effectiveness of cultural elements in shaping students' national identity and patriotic values ​​in both countries. Novelty: This study is novel in its comparative approach, highlighting similarities and differences in cultural learning strategies implemented in elementary schools in Indonesia and Turkey. Methods: This study uses a qualitative approach with a case study, involving observation, interviews with teachers, and content analysis of curriculum documents. Results: Both countries integrate local traditions, historical narratives, and national symbols in their education systems, but with different pedagogical approaches. While Indonesia emphasizes local wisdom and folklore, Turkey combines historical events and civic education. Conclusion: Culture-based learning contributes significantly to nurturing nationalism, and integrating local pedagogical strategies can further enhance students' sense of national identity.